An improved inventory of polychlorinated biphenyls in China: A case study on PCB-153. (June 2018) - Xu, Yue; Tian, Chongguo; Wang, Xiaoping; Ma, Jianmin; Tang, Jianhui; Chen, Yingjun; Li, Jun; Zhang, Gan
Abstract: Emission inventory of pollutants is essential for the environmental fate study and management of the pollutant. To construct a reasonable PCB (polychlorinated biphenyls) inventory in China, this study estimates PCB usage and emission using power generating capacity, installed capacity of power plants and transformer substations, population density and GDP as surrogates. Inventory of representative PCB (PCB-153) with a resolution of 1/4° latitude × 1/4° longitude in China from 1952 to 2005 was generated and assessed as an example. Totally, about 20.3 kt PCBs were applied in China, of which 179 t were PCB-153. By the end of 2005, most of them (56.4%) were emitted into the soil, 2.7% entered the air, and about 20.8% was sealed in storage site or still in service. Historical emissions exhibited increasing trends after 1968, 1984 and 1994, which were mainly associated with usage or disposal processes. Although primary emission has been declined since 2005, the influence of secondary emission from soils, unintentionally produced PCBs (UP-PCB), and reemission from storage sites could be a long-lasting issue in the future. This new emission inventory improves previous PCB emission inventory significantly, which underestimated PCB emission in China considerably. Graphical abstract: Image 1 Highlights: Historically, about 179 ton PCB-153 were applied in China. Until 2005, major part (56.4%) of PCB-153 were emitted into the soil. Previous inventory may underestimate PCB emission in China.